Photocatalytic degradation of chlorinated ethenes - Kyoichi Oki; Sachiko Tsuchida; Hiromasa Nishikiori; Nobuaki Tanaka; Tsuneo Fujii (International Journal of Photoenergy)
Degradation of three chlorinated ethenes, trichloroethylene, trans-1,2-dichloroethylene and cis-1,2-dichloroethylene, by UV-light irradiated TiO2 catalyst prepared by the sol-gel method in dry air at ambient temperature have been examined by using FTIR measurement. The chlorinated ethenes rapidly decomposed to produce dichloroacethyl chloride, CO, HCl, and COCL2. For trans- and cis-1,2-DCE systems isomerization to each other is found to be the first step of the degradation. The C = C bond of the chlorinated ethenes interacts directly with TiO2 site and, consequently, the degradation results in several products on the catalyst surface in these systems.